A Glimpse of Inflammation and Anti-Inflammation Therapy in Diabetic Kidney Disease - Liu, Chongbin; Yang, Ming; Li, Li; Luo, Shilu; Yang, Jinfei; Li, Chenrui; Liu, Huafeng; Sun, Lin (Frontiers in Physiology, 2022)
Recently, in vitro and in vivo studies have demonstrated that inflammation plays an important role in the pathogenesis of diabetic kidney disease (DKD). A variety of complex pro-inflammatory cytokines and related signaling pathways were involved in the procession of DKD. In addition, some clinical anti-hyperglycemic drugs etc. alleviate the progression of DKD through its anti-inflammation function, but there currently lacks of systematic description. This review focuses on the novel pro-inflammatory signaling pathways in DKD, which conclude NF-κB signaling pathways, inflammasome activation, mtDNA release, HIF signaling pathway and AMPK signaling pathways. We also discuss the related anti-inflammation mechanism of Metformin, Finerenone, SGLT2 inhibitors and Chinese Medicine.